Optical properties of organic carbon and soot produced in an inverse diffusion flame. (November 2017) - Russo, C.; Apicella, B.; Lighty, J.S.; Ciajolo, A.; Tregrossi, A.
Abstract: The carbonaceous particulate matter (soot plus organic carbon) sampled downstream of an ethylene inverse diffusion flame (IDF) was chemically and spectroscopically analyzed in detail. In particular, the H/C ratio, the UV–Visible absorption coefficient and Raman parameters were measured and found to be representative of a highly disordered sp 2 -rich carbon as the early soot sampled in a premixed flame. In contrast, the optical band gap was found to be relatively low (0.7eV), closer to the optical band gap of graphite than to that of medium-sized polycyclic aromatic hydrocarbons (>2eV) which are widely considered to be soot precursors and are mostly contained in the organic carbon. The significance of the optical band gap as signature of different structural levels (nano-, micro- and macro-structure) of sp 2 -rich aromatic disordered carbons was critically analyzed in reference to their molecular weight/size distribution. The relevance of the optical band analysis to the study of the soot formation mechanism was also highlighted. Graphical abstract: